Penerjemahan Mesin dalam Pembelajaran Bahasa dan Penerjemahan Profesional: Tinjauan Literatur - Hajar, Siti (Jurnal Penerjemahan, 2023)
Machine translation (MT) is fundamental in translating from source to target languages. This demand has indicated exponential growth over the past years due to the rapid development of this artificial intelligence. With the increasing use of MT, where the MT itself has its benefits and downsides, researchers have actively conducted MT research for more than seven decades. This paper addresses three key research questions: the theoretical frameworks adopted in MT studies, the benefits and drawbacks of MT in both language learning and professional translation. After discussing and summarizing the three key research questions, the author concludes and ponders implications for MT users and trainers and new directions for future research. Keywords: Machine translation; translation in language learning; professional translation; benefits of MT; downsides of MT.